Analysing the impact of taxi violence on commuters in South Africa - Mmakwena, Modipa (Technium Social Sciences Journal, 2022)
Taxi violence in South Africa was the tool that the apartheid regime used to pursue their interest by dividing the people so that they could acquire what they needed (Sekhonyane and Dugard, 2004:15). Taxi violence is one of the most burning issues faced by Department of Transport, Police, commuters and taxi industry in South Africa. This industry plays a vital role in commuting people to and from work or different destinations, and in most cases it is caught in the wrong doing in terms of fighting for routes where many innocent lives are lost due to infighting. The inability by government to regulate taxi industry is a serious problem for taxi operators, taxi associations, commuters and society. The deregulation of taxi industry brought many problems such as conflict, violence and mafia type assassinations in South Africa. This article focus on preventive measures to curb taxi violence in South Africa. This article utilised qualitative, case study based approach and the approach is supported by analysis of primary and secondary sources. The article further draws on the findings from the world on taxi violence and formulate steps to counteract taxi violence in South Africa. The research based key steps leading to the prevention of taxi violence in South Africa. The first process related to regulation of taxi industry, awareness campaigns on taxi operations, the control of routes and multidisciplinary investigation team should be established to overcome taxi violence in South Africa.